2007
DOI: 10.1158/0008-5472.can-06-4554
|View full text |Cite
|
Sign up to set email alerts
|

Nonclassic Functions of Human Topoisomerase I: Genome-Wide and Pharmacologic Analyses

Abstract: The biological functions of nuclear topoisomerase I (Top1) have been difficult to study because knocking out TOP1 is lethal in metazoans. To reveal the functions of human Top1, we have generated stable Top1 small interfering RNA (siRNA) cell lines from colon and breast carcinomas (HCT116-siTop1 and MCF-7-siTop1, respectively). In those clones, Top1 is reduced f5-fold and Top2A compensates for Top1 deficiency. A prominent feature of the siTop1 cells is genomic instability, with chromosomal aberrations and histo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
95
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 44 publications
7
95
4
Order By: Relevance
“…Thus, it is possible that Top1 protein reduction may disturb splicing of S region transcripts and prolong the half life of S region transcripts, leading to the formation of frequent R-loop and consequent non-B DNA structures in the S region (3,32). In support of this hypothesis, the reduction of either Top1 or ASF induces genomic instability (17,32). In fact, we observed that the single stranded fraction of the S region was augmented by Top1 knockdown.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Thus, it is possible that Top1 protein reduction may disturb splicing of S region transcripts and prolong the half life of S region transcripts, leading to the formation of frequent R-loop and consequent non-B DNA structures in the S region (3,32). In support of this hypothesis, the reduction of either Top1 or ASF induces genomic instability (17,32). In fact, we observed that the single stranded fraction of the S region was augmented by Top1 knockdown.…”
Section: Discussionsupporting
confidence: 66%
“…A specific inhibitor of Top1, camptothecin (CPT) can be intercalated into this transient cleavage complex of Top1 and DNA to block Top1's catalytic function while CPT does not affect free Top1 (16). Curiously, the reduction of Top1 by RNA mediated knockdown in cultured cells causes the genome-wide instability (17). Activation-induced cytidine deaminase (AID) is essential for CSR and involved in S region cleavage, but its molecular mechanism is unknown (12,13,18,19).…”
mentioning
confidence: 99%
“…Recently a small study including 28 patients with mBC used a multi-omic molecular profile (MMP) including Topo1 to identify potential therapeutic targets and select individualized treatment. All patients were heavily pretreated with at least three prior treatment regimens (range [3][4][5][6][7][8][9][10][11][12]. Based on the MMP 14 patients were treated with irinotecan or irinotecan plus fluorouracil.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, although using similar technologies, other studies have not found Top1 protein predictive of response in the metastatic setting. 7,8 Reduced levels of Top1 in BC cells have been associated to decreased sensitivity to camptothecin 9 and a single small (n 5 22) clinical study has reported increased levels of Top1 protein in primary tumors from patients with BC. 10 Furthermore, high TOP1 gene copy numbers in BC cell lines have been found to be associated with increased sensitivity to SN38, which is the active metabolite of irinotecan.…”
mentioning
confidence: 99%
“…The CD133 + clonal cells and the CD133 -clonal cells display differential gene expression profiles. Using Affymetrix U133-plus-2-Genechips that contain the probe sets against the transcripts of 17,942 different genes with their Human Genome Organization (HuGO) names, 13 we detected mRNA levels in the purified CD133 + clonal cells and the purified CD133 -clonal cells. A list of 326 candidate genes was produced by taking the changes common to two independent experiments ( Fig.…”
Section: Characterization Of the Conversionmentioning
confidence: 99%